The creative function of the two chambers of Polish Parliament as a representative of the Nation - Stadniczeńko, Stanisław Leszek (The Opole Studies in Administration and Law, 2016)
The author undertakes to establish the legal title to performing the creative function by the two chambers of Polish Parliament as a representative of the nation. The article describes the competence of the Sejm and the Senate as the constitutional authorities of the State that perform the creative function. The creative function of the Parliament may be considered as a result of the activities of this institution for other institutions as well as the functioning of the whole system. Voters’ crisis of confidence in the both chambers of Polish Parliament may also be understood as a crisis of its functions.